A hybrid technique for management of post-traumatic aniridia and aphakia. - Randazzo, Viviana; Marchese, Vincenzo (Acta Biomedica Atenei Parmensis, 2022)
We report a case of a 35-year-old woman who suffered blunt ocular injury, causing total aniridia and aphakia associated with rhegmatogenous retinal detachment (RRD). RRD was treated with pars plana vitrectomy, a suture net with Ethilon 10-0 to prevent the silicone oil (SO) to enter the anterior chamber and SO tamponade. Implantation of a foldable prosthetic iris (Ophtec Model C) was fixed to the sclera with a hybrid technique, the Hoffmann corneoscleral pocket technique associated with Canabrava’s double flanged technique to address both pathologies of aniridia and secondary aphakia. Cosmetic result was satisfactory, patient’s visual acuity increased and no complications were observed during the follow-up. Canabrava technique simplifies and improves the fixation of the iris-intraocular lens complex to the sclera and the corneoscleral pocket technique is a safe option that does not require scleral flaps or knots, avoiding further conjunctival trauma and ensuring good stability of the implant.